THE ROLE OF INVESTMENT PROMOTION AGENCIES IN ATTRACTING FOREIGN DIRECT INVESTMENT - Algirdas Miškinis; Mariya Byrka (Ekonomika, 2015)
Establishing an investment promotion agency (IPA) has become a very popular institutional approach in the strategic promotion of foreign direct investment (FDI) across nations and regions worldwide. In this article, we examine the role of IPAs in improving the FDI environment and promoting inward FDI. The task of the article is, with the help of qualitative methods of research, to determine the promotion techniques and tools that lead to a better FDI performance and verify them in the cases of such investment promotion agencies as Invest Lithuania and Invest in Lviv Region (Ukraine).